ANALISIS FAKTOR DAYA TARIK WISATA CURUG KEMBAR BINUANG DI DESA RAKSABAYA KECAMATAN CIMARAGAS KABUPATEN CIAMIS: Array - Eet Saeful Hidayat; Lina Marliani; Rifki Agung Kusuma (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The regional tourism sector has a strategic and sexy role because it can support regional revenue, regional development and make a significant contribution to the economic and social development of the surrounding community. However, these expectations are not easy to achieve because many factors play a role, such as shared perceptions of stakeholders, inadequate human resource competencies, weak support from local governments and the attractiveness of destinations. This study aims to identify the factors that attract visitors to the Curug Kembar Binuang tourist attraction in Ciamis Regency, West Java, using qualitative descriptive methods, analysis using survey techniques, while the target population is 2 (two) groups, namely tourism object managers and visitors. / tour. The results showed that based on the results of the factor analysis carried out, it was identified 3 factors that became the attraction of choosing Curug Kembar Binuang as a tourist destination to visit, namely: development of tourist attractions through exploring regional potential, providing facilities and infrastructure to support tourism objects so as to provide comfort, and accessibility that is easy to use and reach by visitors/tourists.